2022
DOI: 10.3390/en15114130
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model for Phase Synchronization of a Pair of Vertical-Axis Wind Turbines

Abstract: The phase-synchronized rotation of a pair of closely spaced vertical-axis wind turbines has been found in wind tunnel experiments and computational fluid dynamics (CFD) simulations. During phase synchronization, the two wind turbine rotors rotate inversely at the same mean angular velocity. The blades of the two rotors pass through the gap between the turbines almost simultaneously, while the angular velocities oscillate with a small amplitude. A pressure drop in the gap region, explained by Bernoulli’s law, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Their CFD analysis considering the time-varying rotor speed, for the first time, simulated the synchronization operation of twin rotors and showed the alternation in the angular velocities of two rotors. Furukawa et al [36] developed an analytical model considering the pressure fluctuation (or increase in flow velocity) observed in the gap region between twin rotors in the above experiments and CFD analyses. The model successfully demonstrated the alternation in the angular velocities of two rotors and showed that the period of the variation in rotor speed depended on the strength of the interaction between the two rotors.…”
Section: Introductionmentioning
confidence: 99%
“…Their CFD analysis considering the time-varying rotor speed, for the first time, simulated the synchronization operation of twin rotors and showed the alternation in the angular velocities of two rotors. Furukawa et al [36] developed an analytical model considering the pressure fluctuation (or increase in flow velocity) observed in the gap region between twin rotors in the above experiments and CFD analyses. The model successfully demonstrated the alternation in the angular velocities of two rotors and showed that the period of the variation in rotor speed depended on the strength of the interaction between the two rotors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors show, using a surrogate model, that turbine spacings can be optimised based on the resulting wake dynamics. Another study by Furukawa et al [15] proposes a model for quantifying the interacting torques as a result of the VAWT rotor phase synchronisation. More advanced studies on floating VAWT wake interactions, taking into account pitching motions, can be found in Kuang et al [16].…”
mentioning
confidence: 99%